Assessment of Indoor Air Pollutants Generated from Energy Sources in Rural Households of Chamarajanagar Taluk - Komala H.P.; Devi Prasad A.G. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Most of the rural households in India use biomass for cooking and heating purposes. The biomass combustion emit huge amount of pollutants which causes harmful effects on environment and on human health. The present study was conducted to assess the level of indoor air pollutants during cooking in rural households. The investigation was carried out in 50 randomly selected rural households of Chamarajanagar taluk that use biomass, kerosene and LPG as cooking fuels. The concentration of CO and CO2 were measured by using battery operated CO and CO2 meter which works on NDIR method. The sampling of suspended particulate matter was done by gravimetric method using handy sampler 821. The particulate matters were collected on micro fiber filter paper which is subjected to morphological analysis by SEM. The recorded mean concentration of CO (46.67 ppm) for traditional cook stove was higher than the WHO standard (35ppm). The results have shown that the emission of CO, CO2 and SPM concentrations were more for biomass fuels as compared to kerosene and LPG fuels. The suspended particulate matters were found to be spherical, angular, cluster and irregular in shapes. The study has shown that utilization of biomass fuels under poorly designed cook stove is the main factor responsible for increase of indoor air pollutants.